Inhibitory effects of Ponciri Fructus on testosterone-induced benign prostatic hyperplasia in rats - Jeon, Woo-Young (BMC Complement Altern Med, 2017)
BACKGROUND: Benign prostatic hyperplasia (BPH) is non-cancerous condition of enlargement of the prostate, a common occurrence in older men. The immature fruits of Poncirus trifoliata (L.) Rafinesque (Rutaceae), Ponciri Fructus are widely used in traditional oriental medicine for the therapy of various diseases. However, little is known about the mechanism underlying the pathogenesis of BPH. In the present study, we investigated the protective effects of a Ponciri Fructus extract (PFE) on the development of BPH in a in a rat model of BPH induced by testosterone propionate (TP). METHODS: Male Sprague Dawley rats were used as a model of BPH after its induction by daily subcutaneous injections of TP/corn oil, for a period of four weeks. PFE was administrated daily 1 h before TP/corn oil injection by oral gavage at a dose level of 200 mg/kg during the 4 weeks of TP/corn oil injections. All rats were sacrificed at the end of the experiment, we measured the relative prostate weight, the levels of testosterone and dihydrotestosterone (DHT), histological changes, activities of antioxidant enzymes (catalase, glutathione peroxidase, glutathione reductase, and superoxide dismutase), and expression of proliferating cell nuclear antigen (PCNA). In addition, we also measured the inhibition (%) of 5α-reductase in the prostatic tissue. RESULTS: Our findings indicate that PFE significantly inhibited the development of BPH; decreased the relative prostate weight, the level of testosterone and DHT in serum and prostatic tissue, prostatic hyperplasia, expression of PCNA, and increased the antioxidant enzymes. Moreover, PFE showed a weak inhibitory activity on 5α-reductase. CONCLUSIONS: These results suggest that PFE may be used as a therapeutic agent for BPH via antiproliferative and antioxidant effects.